ASSESSMENT OF COAGULATION PROFILE IN PATIENTS WITH LIVER CIRRHOSIS AND ATRIAL FIBRILLATION - Baylo, Alіna; Shypulin, Vadym; Chernyavskyi, Volodymyr; Parunyan, Luiza (The Ukrainian Scientific Medical Youth Journal, 2021)
The comorbid course of liver cirrhosis and atrial fibrillation causes higher levels of hospitalizations, mortality and ischemic stroke. According to current data, hemostasis in patients with liver cirrhosis is in a rebalanced dynamic state, but there are no data on the effect of atrial fibrillation on the hemostasis in patients with liver cirrhosis. Aims of the study. To assess abnormalities in primary, secondary haemostasis and fibrinolytic system in patients with liver cirrhosis and atrial fibrillation by using standard laboratory coagulation parameters and to investigate their changes depending on the stage of liver cirrhosis A, B, C according to Child-Pugh score. Materials and methods. A cross-sectional prospective study was conducted with the inclusion of 106 patients aged 42 to 83 years: group I (n = 70) - with liver cirrhosis and atrial fibrillation, II (n = 36) - with liver cirrhosis, which were distributed depending on the Child- Pugh score stages of cirrhosis and 20 healthy individuals. The levels of platelets, activated partial thromboplastin time, international normalized ratio, prothrombin time, thrombin time, fibrinogen, D-dimer were assessed on a Steellex M200 coagulometer. Statistical analysis (IBM SPSS Statistics) was performed. Results. The level of platelets in patients of group I was reduced by 37.4% (200 ± 8.33 vs. 274.7 ± 3.4; p,000.001), an activated partial thromboplastin time was prolonged by 38.6% (44.35 ± 1.39 vs. 32.01 ± 0.63, p˂0.001), prothrombin time was prolonged by 73.5% (19.4 ± 0.87 vs. 11.18 ± 0.53, p˂0.001), thrombin time was prolonged by 2.07 (25,7 ± 1.31 vs. 12.4 ± 0.66, p˂0.001), the international normalized ratio was increased by 24.3% (1.38 ± 0.04 vs.1.11 ± 0.01, p˂0.001) compared to control. The fibrinogen level was 20.9% higher (4.17 ± 0.17 vs. 3.45 ± 0.11, p˂0.001)than in control group and was 83.7% higher (4.17 ± 0.17 vs. 2.27 ± 0.13, p˂0.001) than in group II. The D-dimer level was 83% higher than in control (675 ± 22.3 vs. 368.8 ± 21.85, p˂0.001) and 44% higher (675 ± 22.3 vs. 469 ± 37.18, p ˂0.001) compared with group II. Conclusions. In patients with liver cirrhosis and atrial fibrillation abnormalities of primary hemostasis are detected due to decrease of platelets on the background of portal hypertension. At the secondary stage of hemostasis indicators of external and internal coagulation mechanisms are prolonged due to the reduced synthesis of coagulation factors by the liver. Increased level of fibrinogen is determined at the stage of compensated and subcompensated cirrhosis with a gradual decrease at the stage of decompensation. The high activity of the fibrinolytic system is observed due to increase in the D-dimer levels, which may indicate a prothrombotic state in these patients.